Where do all the subtypes go? Temporal dynamics of H8–H12 influenza A viruses in waterfowl. Issue 2 (14th August 2018) - Wille, Michelle; Latorre-Margalef, Neus; Tolf, Conny; Halpin, Rebecca; Wentworth, David; Fouchier, Ron A M; Raghwani, Jayna; Pybus, Oliver G; Olsen, Björn; Waldenström, Jonas
Abstract: Influenza A virus (IAV) is ubiquitous in waterfowl. In the northern hemisphere IAV prevalence is highest during the autumn and coincides with a peak in viral subtype diversity. Although haemagglutinin subtypes H1–H12 are associated with waterfowl hosts, subtypes H8–H12 are detected very infrequently. To better understand the role of waterfowl in the maintenance of these rare subtypes, we sequenced H8–H12 viruses isolated from Mallards ( Anas platyrhynchos ) from 2002 to 2009. These rare viruses exhibited varying ecological and phylodynamic features. The Eurasian clades of H8 and H12 phylogenies were dominated by waterfowl sequences; mostly viruses sequenced in this study. H11, once believed to be a subtype that infected charadriiformes (shorebirds), exhibited patterns more typical of common virus subtypes. Finally, subtypes H9 and H10, which have maintained lineages in poultry, showed markedly different patterns: H10 was associated with all possible NA subtypes and this drove HA lineage diversity within years. Rare viruses belonging to subtypes H8–H12 were highly reassorted, indicating that these rare subtypes are part of the broader IAV pool. Our results suggest that waterfowl play a role in the maintenance of these rare subtypes, but we recommend additional sampling of non-traditional hosts to better understand the reservoirs of these rare viruses.